Faktor yang memengaruhi penetapan Hotel X sebagai wedding venue - Sriyani, Vera (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
The wedding is one of the most important events for couples, so mostly they want their wedding event as perfect as possible. Choosing a wedding venue is the first step to preparing a wedding. The purpose of this research is to determine factors that affect the selection of a wedding venue at Hotel X. The respondents of this research are 203 prospective wedding couples who came to Hotel X. The method used in this research is multivariate analysis. This study obtained data via questionnaires and used statistical tests such as F-test, R Square (R2)-test, and T-test. The result of this study shows location, atmosphere, facility, food, service, and price are factors which has a significant influence on prospective wedding couple’s purchase decisions.